2015
DOI: 10.1111/jnc.13117
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous arachidonic acid mediates permeability of human brain microvessel endothelial cells through prostaglandin E2 activation of EP3 and EP4 receptors

Abstract: The blood-brain barrier, formed by microvessel endothelial cells, is the restrictive barrier between the brain parenchyma and the circulating blood. Arachidonic acid (ARA; 5,8,11,14-cis-eicosatetraenoic acid) is a conditionally essential polyunsaturated fatty acid [20:4(n À 6)] and is a major constituent of brain lipids. The current study examined the transport processes for ARA in confluent monolayers of human brain microvascular endothelial cells (HBMEC). Addition of radioactive ARA to the apical compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…In brain endothelial cells, exposure to both bacterial endotoxin as well as inflammatory cytokines results in the production and release of PGE 2 [8,9,25]. Within the brain microvasculature, PGE 2 promotes increased permeability and reduced BBB integrity [7,8]. The effects of increased PGE 2 within the brain are associated with a number of pathologies, including pyretic response to bacterial infection [26], HIV-and Alzheimer's disease-related microglial response and cognitive deficits [27,28], neurotoxicity in stroke and traumatic brain injury [29].…”
Section: Fatty Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…In brain endothelial cells, exposure to both bacterial endotoxin as well as inflammatory cytokines results in the production and release of PGE 2 [8,9,25]. Within the brain microvasculature, PGE 2 promotes increased permeability and reduced BBB integrity [7,8]. The effects of increased PGE 2 within the brain are associated with a number of pathologies, including pyretic response to bacterial infection [26], HIV-and Alzheimer's disease-related microglial response and cognitive deficits [27,28], neurotoxicity in stroke and traumatic brain injury [29].…”
Section: Fatty Acidmentioning
confidence: 99%
“…Such bioactive lipids may play a role in autoregulation of the cerebral microvasculature under both physiological and pathophysiological conditions. For example, we recently demonstrated that incubation of confluent monolayers of human brain microvessel endothelial cells with arachidonic acid (ARA) resulted in the generation of the oxylipin prostaglandin (PG) E 2 , which plays a role in regulating brain microvessel permeability [7][8][9]. However, there are potentially many other such oxylipins with biological activity that have yet to be identified in the brain endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to restore metabolic balance, cortical neurons including interneurons and astroglia are thought to release of a variety of neurotransmitters including NO, carbon monoxide, adenosine, hydrogen ions, potassium ions, and lipoxygenase products known to alter cerebral vascular tone (Cauli et al, 2004; Vaucher et al, 2000; Zonta et al, 2003; Filosa et al, 2006; Koehler et al, 2006; Busija et al, 2008). Independent of vascular tone, these signaling molecules also directly affect endothelial cell signaling pathways (De Caterina et al, 1995; Jozkowicz et al, 2003; Erlinge and Burnstock, 2008; Dalvi et al, 2015; Mark et al, 2001). Moreover, the close association between cerebral blood vessels and neurons (Hawkins and Davis, 2005) facilitates 2-way communication between cortical neurons and endothelial cells comprising the blood vessels.…”
Section: 1 Cortical Spreading Depressionmentioning
confidence: 99%
“…With this background, I will highlight the significant advances in the field that are found in a new publication from the Hatch group at the University of Manitoba (Dalvi et al . ). In this work, they demonstrate using human microvascular endothelial cell cultures, a model of the human BBB, that a physiologically relevant concentration of ARA induces an increase in permeability in this BBB model.…”
mentioning
confidence: 97%